2022
DOI: 10.1029/2022tc007274
|View full text |Cite
|
Sign up to set email alerts
|

Space and Time Variability of Detachment‐ Versus Ramp‐Dominated Thrusting: Insights From the Outer Albanides

Abstract: Despite their markedly different structural setting, the northern and southern outer Albanides share a common tectonic evolution from detachment‐dominated to ramp‐dominated, basement‐involved thrusting. The former process (mainly Oligocene to Miocene) is essentially related with the occurrence of a thick décollement level represented by Triassic evaporites, while the latter involves basement ramps splaying out from a middle crustal décollement. As this weak crustal layer is inherited from the Mesozoic rifting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…Local shear failure led to localization of compression in conjugate thrusts and other minor structures, which were then involved in folding. This generally occurs in thick competent units (Mazzoli et al., 2022; Morley, 1994; Price & Cosgrove, 1990; Ramsay, 1981). In the northwestward pericline of the Pag anticline, older WNW‐ESE striking, mesoscale thrust fault zones and associated contractional deformation structures are cross‐cut by NW‐SE striking thrusts, backthrusts and fold‐accommodation structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Local shear failure led to localization of compression in conjugate thrusts and other minor structures, which were then involved in folding. This generally occurs in thick competent units (Mazzoli et al., 2022; Morley, 1994; Price & Cosgrove, 1990; Ramsay, 1981). In the northwestward pericline of the Pag anticline, older WNW‐ESE striking, mesoscale thrust fault zones and associated contractional deformation structures are cross‐cut by NW‐SE striking thrusts, backthrusts and fold‐accommodation structures.…”
Section: Discussionmentioning
confidence: 99%
“…After significant bed rotation fold locking likely produced strain hardening. These structures eventually propagated into thrusts and backthrusts showing high cutoff angles in the fold limbs and into out of syncline thrusts (Mazzoli et al., 2022; Morley, 1994; Price & Cosgrove, 1990; Ramsay, 1981). Fold tightening was also characterized by strike‐slip reactivation of previously formed prefolding and synfolding deformation structures, including conjugate strike‐slip shear fracture arrays, and rotated thrust fault zones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in folding being dominant with respect to thrusting in terms of modes of deformation. Recent studies further suggested that the process of detachment folding is equivalent to that of buckle folding (Butler et al., 2019; Mazzoli et al., 2022). Multilayer buckling is well known to be governed by both viscosity contrasts and thickness of the mechanically dominant competent units (control units sensu Butler et al., 2019) and, more in detail, by the geometrical arrangement and relative thickness of competent and incompetent beds (Ramsay & Huber, 1987).…”
Section: Introductionmentioning
confidence: 99%